'Helping people is real Jainism': class privileged diasporic Jains affirm citizenship and multiple belongings through transnational philanthropy to a Jain faith-based organisation in India. Issue 2 (2nd July 2020) - Shah, Bindi V.
ABSTRACT: The dominant diaspora-development discourse privileges rational imperatives and focuses on remittances to households while ignoring diaspora philanthropy to organisations. In India, religious organisations receive significant levels of diaspora philanthropy yet the motivations and cultural meanings behind such transfers, or its transnational dimensions are little understood. I examine these themes through in-depth interviews with 24 Jains in UK, U.S.A and Singapore who have supported Veerayatan, a Jain faith-based organisation established by Jain nuns to deliver welfare services in India over an extensive period. I contend that diasporic Jains display a hybrid logic of philanthropy; humanitarian ideals intersect with shared Jain religious norms to motivate giving. Support for Veerayatan is sustained through social capital; embeddedness in lateral networks of co-religionists as well as ties with the nuns in the homeland. This transnational engagement is a marker of citizenship and multiple belongings, of being British, American or Singaporean differently for class-privileged diasporic Jains.